Effectiveness of Employee Performance in the Medical Record Section (Case Study of RST Bhakti Wira Tamtama) - Insiana Tulus Sukma; Bambang Wahyono (Jurnal EduHealth, 2023)
Having a medical record officer with good performance is the key to implementing a quality medical record because it is an indicator of the quality standard of health services in hospitals. This study aims to determine the level of performance effectiveness of medical record officers by carrying out multiple assignments at RST Bhakti Wira Tamtama. This research is a descriptive qualitative research with a case study approach. The data analysis technique in this study uses the Miles and Huberman interactive analysis model. There were 13 informants in this study, consisting of 4 medical record officers who had dual assignments, while 9 triangulation informants consisted of 1 head of medical record room, 4 medical record employees who did not have dual assignments, and 4 nurses at Bhakti Wira Tamtama Hospital. The data collection method in this study is an in-depth interview method. The results of this study found that the performance of medical record employees at RST Bhakti Wira Tamtama with dual assignments was generally not effective as seen from the lack of achievement of several variables, namely work performance variables and job satisfaction variables.